In vitro synergistic antibacterial activity of the essential oil from Zingiber cassumunar Roxb against extensively drug-resistant Acinetobacter baumannii strains - Wongwarut Boonyanugomol; Kairin Kraisriwattana; Kamolchanok Rukseree; Kraisorn Boonsam; Panchaporn Narachai (Elsevier, 2017)
In this study, we determined the antibacterial and synergistic activities of the essential oil from Zingiber cassumunar against the extensively drug-resistant (XDR) Acinetobacter baumannii strains. The antibacterial and synergistic properties of the essential oil from Z. cassumunar were examined by agar disc diffusion tests. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were evaluated by broth microdilution using the resazurin assay. The in vitro time-kill antibacterial kinetics was analyzed using the plate count technique. We found that the essential oil from Z. cassumunar had antibacterial activity against A. baumannii, with MIC and MBC ranging from 7.00 to 9.24 mg/ml. The essential oil could completely inhibit A. baumannii at 1 h, and coccoid-shaped bacteria were found after treatment. In addition, the essential oil had a synergistic effect when combined with antibiotics, e.g., aminoglycosides, fluoroquinolones, tetracyclines, and folate pathway inhibitors. Thus, the essential oil from Z. cassumunar has strong antibacterial and synergistic activities against XDR A. baumannii, which may provide the basis for the development of a new therapy against drug-resistant bacteria. Keywords: Acinetobacter baumannii, Z. cassumunar, Essential oil, Antibacterial activity, Synergism